Pharmacokinetics of gadobenate dimeglumine in children 2 to 5 years of age undergoing MRI of the central nervous system. Issue 4 (8th May 2014) - Pirovano, Gianpaolo; Kirchin, Miles A.; Lorusso, Vito; Patel, Rutu; Shen, Ningyan
<x xml:space="preserve">Abstract</x> Purpose To determine the pharmacokinetic profile of gadobenate dimeglumine in children aged between 2 and 5 years. Materials and Methods Fifteen children scheduled to undergo contrast‐enhanced MRI for suspected disease of the central nervous system received a single intravenous injection of 0.1 mmol/kg gadobenate dimeglumine. Children were stratified into three age groups: 2 to <3 years, 3 to <4 years, and 4 to 5 (i.e., <6 years). Serial blood and urine samples collected at prespecified time‐points before and after contrast administration were analyzed for gadolinium concentrations. Pharmacokinetic parameters were calculated using noncompartmental and compartmental techniques. Results Mean values of 65.7 μg/mL for highest blood gadolinium concentration, 0.2 L/h/kg for blood clearance, 0.32 L/kg for steady‐state volume of distribution, and 1.2 h for terminal elimination half‐life were determined across all age groups combined. On average, more than 80% of the dose was eliminated in the urine during the first 24 h after administration. All pharmacokinetic parameters were similar between age groups and no effects of gender were noted. No adverse events considered related to gadobenate dimeglumine administration were reported. Conclusion In terms of pharmacokinetic profile no dosage adjustment from the approved adult gadobenate dimeglumine dose of 0.1 mmol/kg bodyweight is necessary in children aged between 2 and 5 years. J. Magn. Reson. Imaging 2015;41:1096–1103. © 2014 Wiley Periodicals, Inc.